2022
DOI: 10.1186/s40478-022-01426-4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo differences in neurovirulence between D614G, Delta And Omicron BA.1 SARS-CoV-2 variants

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is associated with various neurological complications. Although the mechanism is not fully understood, several studies have shown that neuroinflammation occurs in the acute and post-acute phase. As these studies have predominantly been performed with isolates from 2020, it is unknown if there are differences among SARS-CoV-2 variants in their ability to cause neuroinflammation. Here, we compared the neuroinvasiveness, neurotropism and neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 67 publications
9
32
0
Order By: Relevance
“…1d, Brains). However, consistent with previous reports 58,81 , the majority (80%) of BA.1 infected mice showed no symptoms, with no virus detected in the brains of symptom-free animals (Fig. 1d, Brains).…”
Section: Resultssupporting
confidence: 92%
“…1d, Brains). However, consistent with previous reports 58,81 , the majority (80%) of BA.1 infected mice showed no symptoms, with no virus detected in the brains of symptom-free animals (Fig. 1d, Brains).…”
Section: Resultssupporting
confidence: 92%
“…The viral protein and RNA of SARS‐CoV‐2 were detected scattered throughout the brain tissues of died and survived patients, and infected K18‐hACE2 mice 47,48 . Moreover, SARS‐CoV‐2 may employ olfactory neurons or other bundles to enter the central nervous system from the peripheral nervous system or through the blood–brain barrier 49,50 . Alterations in immune system might be responsible for fatigue, as SARS‐CoV‐2 could reach the hypothalamus via the olfactory pathway, which led to the production of pro‐inflammatory cytokines, and then caused headache and fatigue 25 .…”
Section: Manifestations Of Long Covid In Multiple Organsmentioning
confidence: 99%
“…The sustentacular cells in the olfactory epithelium highly express TMPRSS2, and omicron may have a low tropism on these cells, thereby reducing the frequency of anosmia 164 . The experiment based on human‐induced pluripotent stem cells (hiPSC) derived neurons culture, hACE2 transgenic mice and hamster infection model showed that compared with delta and D614G mutant, the neurotropism, neuro‐invasion, and neurovirulence of omicron are decreasing, 50 which may be explained by the less replication efficiency in the olfactory mucosa of omicron compared with earlier variants 50,166 . Nevertheless, some studies also declared that the neurological and psychiatric outcomes were similar between the delta and omicron infection 167 …”
Section: Possible Differences In Symptoms Of Long Covid Between Diffe...mentioning
confidence: 99%
See 2 more Smart Citations